Left Displacement of the Abomasum in 4 Beef Calves - Oman, R. E.; Streeter, R. N.; Reppert, Emily J.; Chako, C. Z. (My University, 2016)
BackgroundLittle is known about the occurrence rate, underlying etiology or treatment of left displacement of the abomasum in beef calves. ObjectiveDescribe the clinical presentation, diagnosis and treatment of left displacement of the abomasum in 4 beef calves. AnimalsFour client-owned beef breed calves with left displaced abomasum (LDA). MethodsRetrospective case series. Hospital medical records were reviewed to identify all beef breed cattle under the age of 6 months diagnosed with LDA. ResultsFour beef calves were treated for left displacement of the abomasum. All four had a history of decreased appetite and left-sided abdominal distention. Two had recently been treated for necrotic laryngitis and one was being treated for clostridial abomasitis. Ultrasonography confirmed the abomasum to be displaced between the rumen and the left body wall in all calves. The calves were initially treated by rolling to correct the abomasal displacement. The abomasum redisplaced in 3 of 4 calves within 1 hour to 6 days; 1 calf developed a mesenteric volvulus. A right paramedian abomasopexy was performed in all cases. Three of 4 calves grew well and remained in the herd 6-18 months later; 1 calf was euthanized because of complications associated with necrotic laryngitis. Conclusions and clinical importanceLeft displacement of the abomasum should be considered as a differential diagnosis for beef calves with abdominal distention. Concurrent necrotic laryngitis can increase the risk of abomasal displacement in beef calves. Treatment should include surgical correction as rolling is not curative and might be associated with mesenteric volvulus.
Citation: Oman, R. E., Streeter, R. N., Reppert, E. J., & Chako, C. Z. (2016). Left Displacement of the Abomasum in 4 Beef Calves. Journal of Veterinary Internal Medicine, 30(4), 1376-1380. doi:10.1111/jvim.14353
Keywords: Bovine; Calf; Gastrointestinal; Left Displaced Abomasum; Dairy-Cattle; Volvulus